Earthworm optimization algorithm based cascade LSTM-GRU model for android malware detection - Brij B. Gupta; Akshat Gaurav; Varsha Arya; Shavi Bansal; Razaz Waheeb Attar; Ahmed Alhomoud; Konstantinos Psannis (Cyber Security and Applications)
The rise in mobile malware risks brought on by the explosion of Android smartphones required more efficient detection techniques. Inspired by a cascade of Long Short-Term Memory (LSTM) and Gated Recurrent Unit (GRU) networks, optimized using the Earthworm Optimization Algorithm (EOA), this study presents an android malware detection model. The paper used random forest model for feature selection. With a 99% accuracy and the lowest loss values, the proposed model performs better than conventional models including GRU, LSTM, RNN, Logistic Regression, and SVM.. The findings highlight the possibility of proposed method in improving Android malware detection, thereby providing a strong answer in the changing scene of cybersecurity.